Coupling simulation of the fast startup of a centrifugal pump with cavitation in a closed-loop pipeline system. Issue 5 (2nd July 2018) - Meng, Long; Liu, Meng; Zhou, Lingjiu; Wang, Wanpeng; Liao, Cuilin; Zhao, Lice; Li, Tieyou
Abstract : Purpose: Cavitation inside pumps affects not only the steady state fluid flow, but also the unsteady or transient characteristic of the flow. However, cavitation inside pumps under transient processes is difficult to predict when the influence of the pipelines system is considered. In this paper we present a simulation method applied to a centrifugal pump and its related pipeline to analyze the induced unsteady cavitation phenomenon during the startup process. Design/methodology/approach: In order to effectively predict transient processes of a pump and its pipeline system, the simulation method uses a coupled 1D and 3D scheme, which reduces the simulation cost. The simulation of the startup process of a centrifugal pump in a closed-loop pipeline system with and without cavitation has been performed to verify the proposed method. Findings: The evolution of the pressure and flow rate obtained with the simulation method agrees well with the experimental results. It is found that the mass flow rate at the pump inlet and outlet is highly related to the cavitation vapor volume and that the pressure at the outlet of the impeller is greatly influenced by the discharge. Originality/value: The 1D-3D coupling simulation method used in this paper is proven to be highly accurate, efficient and can be used to solve transient processes combined with cavitation or other complex phenomena.